Eksistensi Sistem Pendidikan di Negara Denmark sebagai Salah Satu Negara dengan Pendidikan Terbaik Dunia - Natasya Nurul Lathifa; Mislaini Mislaini; Sri Handayani (Lembaga Pengembangan Kinerja Dosen, 2025)
The Danish education system is an example of an inclusive and individual development-oriented education model, with an emphasis on active and collaborative learning. Primary education in the country is compulsory and free of charge, allowing all children to have equal access to quality education. One of the main strengths of this system is the pedagogical approach that emphasizes creativity, critical thinking, and social skills, which prepares students to face the challenges of the modern world. However, behind these successes, there are some shortcomings, such as inequities in academic achievement among different socio-economic groups and criticism of the evaluation system as lacking transparency. Improvement efforts are ongoing to address these issues, including increased training for educators and the development of a curriculum that is more responsive to student needs. Thus, although the Danish education system has many strengths, challenges remain and require attention to ensure equality and fairness in education for all children.